Estudos pré-clínicos de segurança e eficácia do óleorresina de copaíba e dos extratos da andiroba e jucá para o desenvolvimento de um fitoterápico - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
The Amazon is a region rich in medicinal plants where there are records of at least 1450 species. Some products have great prominence in the daily lives of the Amazonian peoples, such as Carapa guianensis (andiroba), Copaifera reticulata (copaíba) and Libidibia ferrea (jucá), which in areas of difficult access are often used as first-choice remedies in an alternative to drug shortages. Thus, it is known that ethnopharmacology has given rise to several pharmaceutical products that exist today, whether they are herbal medicines or as a base product in the construction of allopathic drugs. Given the recurrent importance that the Amazonian population has given to these three species, we studied the safety and efficacy of the use of these three important natural products most used by traditional Amazonian populations associated in a single topical formulation, proving the safety and efficacy of a new antibacterial herbal medicine. . To achieve these objectives, the collection, botanical identification and chemical characterization of the studied species were carried out. In order to evaluate the safety of the product, several tests were carried out that are recommended by internationally recognized institutions, such as ANVISA and OECD, such as the determination of acute oral toxicity, acute dermal toxicity, dermal toxicity in repeated doses, in vitro eye irritation/corrosion, cytotoxic activity. In order to prove the therapeutic efficacy of the drug, the antimicrobial effect was evaluated through the microdilution test in plates. Additionally, a semi-solid formulation based on Astrocaryum murumuru butter (murumuru) was obtained. In view of the studies, it was observed that the drugs were classified as having a high level of biological safety in the toxicity tests. In the ocular irritation test, the drugs did not show toxicological effects. The cytotoxicity evaluation did not show results that could be considered toxic. In the evaluation of antibacterial activity, the combination of drugs promoted a synergistic effect. When obtaining the formulation, the formation of crystals was observed, confirming the pharmacotechnical compatibility between the tested natural products. Therefore, the drug proposed by this study proved to be safe for use in all tests evaluated and with proven antibacterial activity. Even more, the association of the three natural products together with murumuru butter demonstrated compatibility in the formulation.
Keywords: Plantas medicinais; Fitoterápicos; Estudos toxicológicos; Farmacologia; Sociedade, Natureza e Desenvolvimento